Nexus Between FDI, Agriculture, and Rural Development: Evidence from Asian Countries - Paul, Sujan Chandra; Jahan, Nusrat; Nandi, Ashim Kumar; Rahman, Md Asiqur (Asian Journal of Agriculture and Rural Development, 2021)
The aim of this study is explore the effect of foreign direct investment on agriculture and rural development. For this, panel data of 46 countries from Asia were accumulated for the time frame 1991–2018. The models OLS, POLS, 2SLS, and GMM are employed in this study. The study reveals that there is a favorable association between foreign direct investment and agricultural land as percentage of total land using the models OLS, POLS, 2SLS. In stark contrast, value added for agriculture, forestry, and fishing has an unfavorable association with foreign direct investment in all models employed in the study. Furthermore, female employment in agriculture has a negative association with foreign direct investment in OLS, 2SLS and GMM models, whereas male employment in agriculture has a negative association with foreign direct investment in the POLS model only. Land under cereal production has a favorable association with foreign direct investment in all models except POLS, and permanent cropland has a favorable association with foreign direct investment in all models except GMM. In addition, rural population has a positive relationship with foreign direct investment in OLS, POLS and 2SLS and a negative relationship with foreign direct investment in GMM.